La elasticidad de la demanda de exportaciones ecuatorianas en el periodo dolarizado; The elasticity of demand for Ecuadorian exports in the dollarized period - Daniele Covri Rivera (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2022)
– Exports are a determining variable of the national product so the objective is to perform quantitative estimations, first taking them in an aggregate manner, then by group of products and finally by the main destination market, considering here the four main ones constituted by the US, Chile, Peru and Colombia. Then, the elasticities are found by co-integration models ARDL and VECM, while for the cases of absence of a common stochastic trend the short-term coefficients are obtained through VAR models. At the end, short and long-term ARDL estimates are also made with variables that present a different order of integration, according to the methodology of Pesaran, Shin and Smith (2001), based on the bounds testing approach. The main findings show that in the short term most coefficients are not significant. On the contrary, in the long-term foreign income and the price index are always significant except for Peru. The variables of real exchange rate and volatility are significant only in certain regressions depending on the model considered, although sometimes with unexpected signs. Finally, the regression involving Colombia is totally inconclusive.
Keywords: C22; F10; F14; F31; 330; exports; ARDL; Error Correction Model; VECM